Pengaruh Kualitas Produk Dan Persepsi Harga Terhadap Minat Beli Konsumen Pada Brand Local Sepatu Compass (studi Kasus Pada Pengguna Sepatu Compass Di Kab. Bekasi) - Ridwal, Ridwal; Irwansyah, Iwan; Septa Zahran, Wahidin; Puspa Arum, Suryawati (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This   study   aims   to   determine   the   extent   to   which Product Quality and Price Perception influence the Purchase Intention   of   consumers   for   Compass   shoes   in   Bekasi Regency, both individually and simultaneously. The sample of this study consisted of 150 respondents who are users of Compass   shoes.   The   method   used   in   this   study   is descriptive quantitative. The results of the study show that Product   Quality   has   a   61.9%   influence   on   Purchase Intention, and the t-test indicates a positive and significant influence.   Price   Perception   has   a   53.1%   influence   on Purchase Intention, and the t-test indicates a positive and significant influence. The simultaneous test results indicate that Product Quality and   Price Perception collectively have a   66.0%   influence   on   Purchase   Intention. Based   on   the Anova F-test, the calculated Sig. value is 0.000 < 0.05, thus it   can   be   concluded   that   Product   Quality   (X1)   and   Price Perception (X2) simultaneously influence Purchase Intention (Y).